Dynamic Postural Control in Children: Do the Arms Lend the Legs a Helping Hand? - Hill, Mathew W.; Wdowski, Maximilian M.; Pennell, Adam; Stodden, David F.; Duncan, Michael J. (Frontiers in Physiology, 2019)
There is growing empirical evidence lending support to the existence of an “upper body strategy” to extend the ankle and hip strategies in maintaining upright postural stability among adults. Both postural stability and arm movement functions are still developing in children. Therefore, enquiry concerning arm contribution to postural stability among children is needed. This proof of concept study seeks to determine whether the arms play a functionally relevant role in dynamic postural control among children. Twenty-nine children (girls, n = 15; age, 10.6 ± 0.5 years; height, 1.48 ± 0.08 m; mass, 42.8 ± 11.4 kg; BMI, 19.2 ± 3.7 kg/m2) completed three dynamic balance tests; (1) Y Balance test®, (2) timed balance beam walking test, (3) transition from dynamic to static balance using the Dynamic Postural Stability Index. Each test was performed with free and restricted arm movement. Restricting arm movements elicited a marked degradation in the Y Balance reach distance (all directions, P < 0.001, d = -0.85 to -1.13) and timed balance beam walking test (P < 0.001, d = 1.01), while the Dynamic Postural Stability Index was the only metric that was not different between free and restricted arm movements (P = 0.335, d = -0.08). This study provides direct evidence that the arms play a functionally relevant role in dynamic balance performance among children. These findings may provide the impetus to develop training interventions to improve the use of the arms in activities of daily living.